The impact of TEMU on Korean consumers’ purchasing behavior: An empirical analysis of psychological factors - Chengqin Yang; Zongjing Gu (Environment and Social Psychology, 2025)
This study examines how digital platform environments shape Korean consumers’ psychological responses and purchasing behaviors in the context of cross-border e-commerce, focusing on TEMU as a rapidly expanding marketplace. Grounded in the intersection of technology and psychology, the study conceptualizes the digital marketplace as an information and psychological environment that influences trust, perceived risk, immersion, and ultimately consumers’ well-being and behavioral intentions. It further incorporates Korea’s unique socio-cultural context—characterized by high uncertainty avoidance and strong concern for product authenticity—to explain how environmental cues beyond platform strategies affect consumer decision-making. Using a conceptual model that integrates platform characteristics, promotion strategies, UI convenience, and environmental psychological variables, this study investigates how these factors shape three core psychological mechanisms: trust, perceived risk, and immersion. Immersion is defined as cognitive absorption consistent with flow-based theory, while perceived risk is conceptualized across performance, financial, and privacy dimensions. Survey data were collected from Korean consumers familiar with TEMU,The empirical results show that platform characteristics and UI convenience significantly enhance immersion and trust while reducing perceived risk. Promotion strategies influence behavioral intention indirectly through increased immersion rather than through direct effects. Trust emerges as the strongest predictor of purchase intention, while perceived risk shows a significant mediating effect, demonstrating how consumers’ psychological environments translate digital cues into behavioral outcomes. Contextual moderators shaped by Korea’s regulatory and cultural environment are also discussed.